(untitled) (Economic studies journal, 2022)
The study aimed to identify the extent of the awareness of employees of commercial banks operating in the City of Sirte with the technical and legal aspects of the organization of the work of the banking cheque, and to achieve the goal of the study the researchers conducted a field study on a group of banks operating in Sirte by distributing (40) questionnaires to employees. This study has reached a set of results, the most important of which are: there is an awareness among employees of commercial banks of the technical aspects governing the work of the cheque, as well as there is a lack of awareness among employees of banks of the legal aspects, which may be caused by lack of knowledge of the legal rules governing the cheque.